2016
DOI: 10.14710/jitaa.41.2.53-60
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Most Probable Producing Ability Value for Calf Birth's Performance in Sumba Ongole Cows

Abstract: ABSTRAKEstimasi nilai most probable producing ability (MPPA) sangat penting untuk seleksi induk berdasarkan performan anak-anaknya. Data catatan kelahiran dari 48 ekor induk sapi Sumba Ongole (SO) dan data catatan performan lahir dari 52 ekor pedet digunakan untuk estimasi nilai MPPA. Nilai ripitabilitas (r) yang besar (r>0,30) diperoleh pada sifat panjang badan (PB) lahir. Berat lahir (BL), tinggi gumba (TG) dan lingkar dada (LD) memiliki nilai r yang moderat (0,10 < r < 0,30). Nilai MPPA kumulatif performan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
1
9
2
1
Order By: Relevance
“…The genotype of the GHR|AluI gene was significantly (P<0.05) associated to weaning weight, yearling weight and 18 months weight in Grati-PO cattle but not significant (P>0.05) with birth weight of Grati-PO cattle. The GHR gene was also reported to be significantly associated with weaning weight and daily weight gain in Pasundan cattle (Said et al, 2016), weight gain and carcass weight in Nellore cattle (Bos indicus) and it cross breed (Curi et al, 2006) but it has no effect on reproductive performance in Holstein-Friesian cattle (Hadi et al, 2015). In Bos taurus cattle, the GHR|AluI was found to be associated with birth weight, final wieght and several characteristics of meat quality (Di Stasio et al, 2005;Reardon et al, 2010).…”
Section: Association Of Ghr | Alui Gene With Body Weight In Grati-po ...mentioning
confidence: 99%
“…The genotype of the GHR|AluI gene was significantly (P<0.05) associated to weaning weight, yearling weight and 18 months weight in Grati-PO cattle but not significant (P>0.05) with birth weight of Grati-PO cattle. The GHR gene was also reported to be significantly associated with weaning weight and daily weight gain in Pasundan cattle (Said et al, 2016), weight gain and carcass weight in Nellore cattle (Bos indicus) and it cross breed (Curi et al, 2006) but it has no effect on reproductive performance in Holstein-Friesian cattle (Hadi et al, 2015). In Bos taurus cattle, the GHR|AluI was found to be associated with birth weight, final wieght and several characteristics of meat quality (Di Stasio et al, 2005;Reardon et al, 2010).…”
Section: Association Of Ghr | Alui Gene With Body Weight In Grati-po ...mentioning
confidence: 99%
“…According to Agung et al (2015), the SO cattle has excellent potential as beef cattle based on the ability to gain higher dressing percentage (>50%) compare with other local breeds cattle in Indonesia. Recently, Indonesian farmers can do the selection in the SO cattle based on the MPPA value, breeding value and also performance test (Said et al, 2016a;Said et al, 2016b) but it is need more genetic information to determine the population for the breeding program. However, the superior SO cattle can be generated through the breeding program with early detection system based on the genetic information using molecular technology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the average of dressing percentage in SO bull was 51.73 -52.40 kg (Paskah et al, 2016) and the average of body weight in SO bull at ± 2.5 years age was 353.86 -474.08 kg (Said et al, 2016a). Moreover, the birth weight of SO cattle reached of 23.86±5.68 kg (male) and 19.77±3.19 kg (female) as reported by Said et al (2016b). Selection and breeding program for SO cattle in Indonesia is very important to increase meat production in Indonesia.…”
Section: Introductionmentioning
confidence: 68%
“…Unfortunately, the data records for repeatability estimation in this study was not available. Estimation of r value was needed to estimate most probable producing ability (MPPA) and commonly used for cow's selection (Said et al, 2016b). Heritability value could be used to identify the proportion of genetic variance to phenotypic variance in the population (Warwick et al, 1990).…”
Section: Introductionmentioning
confidence: 99%